Comparison among Steady State Evoked Potential, Tone Burst Auditory Brainstem Response and Pure Tone Audiometry in Hearing Evaluation of Adults with Normal Hearing - Mohd lkhwan Muslimin, Mohd Zainudin (Universiti Sains Malaysia, 2009)
Hearing level can be obtained using subjective or objective tests. An objective test is always preferred if the subjective test cannot be performed appropriately or if its outcomes are questionable. Auditory Brainstem Response (ABR) is a common objective test conducted to predict behavioral hearing thresholds. However, it requires a 'subjective' interpretation of the outcomes by a tester. Steady State Evoked Potential (SSEP) is the latest electrophysiological test invented to serve a similar purpose. SSEP has gained a lot of attention lately because the hearing thresholds are determined objectively. The aim of this study was to make comparison between SSEP and tone burst ABR in relation to Pure Tone Audiometry (PTA) in hearing evaluation of adults with normal hearing. Fifthteen students of USM Health Campus (30 ears, mean age of 23 ± 2.85 years) participated in this study. All subjects had normal hearing in both ears (hearing level of 20 dBHL or below between 250-4000 Hz range), as indicated by PTA. In the main testing, ABR and SSEP thresholds were obtained at frequencies of 500, 1000, 2000 and 4000Hz bilaterally from each subject. Tone bursts used in the ABR employed 2-0-2 cycle configuration, presented at rate of21/s. The presence of wave V at particular levels was determined by testers. SSEP recording was obtained using Sinusoidally Amplitude Modulated (SAM) tones, presented at specific modulation rate (more than 80Hz) for each frequency. SSEP thresholds were determined -using F -statistical analysis. Initial analysis revealed that ABR and SSEP thresholds were significantly different from PTA thresholds, at all frequencies (p<O.OS). Further analysis found that SSEP thresholds showed a higher correlation with behavioral thresholds at all frequencies tested, as compared to ABR. These findings are consistent with previous studies. The clinical usefulness of SSEP over ABR in predicting hearing thresholds of normal subjects is evident, at least in this study.